2020
DOI: 10.3390/molecules25173798
|View full text |Cite
|
Sign up to set email alerts
|

The Curcumin Analogue, MS13 (1,5-Bis(4-hydroxy-3- methoxyphenyl)-1,4-pentadiene-3-one), Inhibits Cell Proliferation and Induces Apoptosis in Primary and Metastatic Human Colon Cancer Cells

Abstract: The cytotoxic and apoptotic effects of turmeric (Curcuma longa) on colon cancer have been well documented but specific structural modifications of curcumin have been shown to possess greater growth-suppressive potential on colon cancer than curcumin. Therefore, the aim of this study is to identify the anti-cancer properties of curcumin analogue-MS13, a diarylpentanoid on the cytotoxicity, anti-proliferative and apoptotic activity of primary (SW480) and metastatic (SW620) human colon cancer cells. A cell viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 119 publications
4
13
0
Order By: Relevance
“…A greater reduction was noted as the dose was increased to 15.14 µM for DU 145 and 15.60 µM for PC-3 cells. In agreement with the recent study, MS13 induced apoptosis by suppressing the Bcl-2 level in colon cancer cells (Ismail et al, 2020). Similar results were reported when a diarylpentanoid, DM-1 treated in melanoma cells and EF24 in hepatocellular carcinoma cells (Liu et al, 2012;Faião-Flores et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A greater reduction was noted as the dose was increased to 15.14 µM for DU 145 and 15.60 µM for PC-3 cells. In agreement with the recent study, MS13 induced apoptosis by suppressing the Bcl-2 level in colon cancer cells (Ismail et al, 2020). Similar results were reported when a diarylpentanoid, DM-1 treated in melanoma cells and EF24 in hepatocellular carcinoma cells (Liu et al, 2012;Faião-Flores et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Besides, MS13 exhibits lower toxicity and highly selective towards PCa cells than normal cells, as indicated by SX values. MS13 showed better cytotoxic activity compared to the parent compound, curcumin against human normal cells, which was consistent with the data described previously (Citalingam et al, 2015;Paulraj et al, 2015;Ismail et al, 2020;Lee et al, 2021). An earlier study reported that FLLL11, which has an identical chemical structure as MS13 was less cytotoxic as curcumin towards human normal cell lines of lung fibroblast (WI-38), bladder smooth muscle and mammary epithelial (non-malignant MCF-10A) (Cen et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…MS13, also known as 1,5-bis(4-hydroxy-3-methoxyphenyl)1,4-pentadiene-3-one, is a mono-ketone derivative that holds α- and β-unsaturated ketone moiety [ 18 ]. This compound has been indicated to exhibit greater cytotoxic effect with lower EC 50 values towards prostate [ 19 ], cervical [ 20 ], colon [ 21 ], glioblastoma, and neuroblastoma [ 22 ] cancer cells. Additionally, MS13 demonstrated its anticancer activity through induction of apoptosis in colon [ 21 ], glioblastoma, and neuroblastoma [ 22 ] cancer cells.…”
Section: Introductionmentioning
confidence: 99%